Systematic determination of the reproductive growth stage most sensitive to high night temperature stress in rice (Oryza sativa) - Coast, Onoriode; Šebela, David; Quiñones, Cherryl; Jagadish, Krishna S.V. (Wiley, 2020)
High night‐temperature (HNT) stress during the reproductive stage of rice (Oryza sativa L.) reduces spikelet fertility and yield by inhibiting important physiological processes. However, specifics such as the period of time that is most sensitive to HNT, is unknown. To investigate this, we conducted four controlled‐environment experiments with two rice cultivars, N22 (HNT tolerant) and WAB56–104 (HNT susceptible). These cultivars were exposed to varying durations and intensities of night temperatures (control, 24°C; HNT, 30 and 35°C) during the reproductive stage. The effect of HNT on spikelet fertility and grain weight varied with duration: spikelet fertility reduced by 47–77% when exposed to HNT for 15 nights, 6–29% when exposed for four nights, and 9–15% when exposed for 5.5 h (pre‐midnight, 1830–0000 h or post‐midnight, 0000–0530 h) for four nights. Spikelet fertility and grain weight were most sensitive to HNT during the first 4 d of anthesis, compared with 1–4, 5–8, and 9–12 d before anthesis. At anthesis, reduction in spikelet fertility did not differ significantly between pre‐ and post‐midnight high‐temperature treatments. Our results suggest that greatest sensitivity to HNT during the reproductive stage occurs during the first 4 d of anthesis, providing a reference for future studies involving HNT tolerance in rice.